Kedudukan Dan Peran Restu Orang Tua Dalam Pernikahan Terhadap Keharmonisan Rumah Tangga - Nurul Azidah (Universitas Kiai Abdullah Faqih (UNKAFA) Gresik, 2025)
The phenomenon of family harmony that every married couple desires and strives for is often hampered because of the parents' approval of the couple. although parental approval is not the only obstacle to the formation of family harmony. The realization of family harmony can be influenced by internal and external factors. However, there are often divisions and disputes between married couples which start from the lack of approval from their parents. In Islamic law, the position of parental approval is not included in the pillars or legal requirements for a marriage. There was no opinion of the ulama' who stated that the validity of marriage requires the blessing of the parents. However, parental blessing plays an important role in creating a harmonious family.